Macroeconomic Analysis for Economic Growth - Jega Ibrahim, Musa (IntechOpen, 2022)
The book discusses the essential principles that guide macroeconomic policy formulation and implementation to stimulate strong economic growth for sustainable development, especially for emerging economies. It includes twelve chapters over three sections: "Macroeconomics of Economic Growth", "Labour Market and Employment", and "The Financial System and Macroeconomic Performance". Key conclusions illustrate that the efficacy of regulatory frameworks to create enabling conditions for nurturing and bolstering robust value-adding production structures anchored on appropriate macroeconomic management are the fundamental building blocks of strong economic growth.